Sally in Three Worlds : An Indian Captive in the House of Brigham Young - Kerns, Virginia, 1948- (Book collections on Project MUSE., 2021)
"This manuscript reconstructs and interprets the life of "Sally," an Indian woman who was captured and enslaved in Utah in 1847. Her captors sold her to a settler who had just arrived in the Salt Lake Valley and she ended up in his father-in-law's house. Sally served as the longtime servant and cook in Brigham Young's household, living and working in the Lion House and Beehive House for over twenty years. Kerns has drawn on a broad range of ethnographic, linguistic, archival, and other documentary evidence from primary sources to present the life of this Native woman"--